Squamous cell carcinoma in a dog - A case report (Indian Journal of Veterinary Pathology, 2025)
A 12-year-old male Labrador was presented at a local multispecialty hospital in Chennai with a history of having a multinodular, ulcerated, greyish-white mass on the right forelimb near the digits for surgical removal. Various samples, including blood samples, peripheral blood smears, fine needle aspiration smears of the mass, and the excised mass were collected and sent to the Centralized Clinical Laboratory at Madras Veterinary College in Chennai for laboratory diagnosis. Hematological studies revealed anemia and leukocytosis with left shift neutrophilia, while no changes were observed in serum biochemical parameters. Cytological findings showed clusters of large neoplastic squamous epithelial cells with faintly basophilic cytoplasm, containing prominent vesicular single to multiple nuclei and nucleoli. Additionally, anisocytosis, anisokaryosis, mitotic figures and tadpole cells were suggested, indicative of squamous cell carcinoma. Histopathological examination revealed neoplastic cells that were polygonal in shape, containing prominent vesicular nuclei, mitotic figures and variable-sized keratin pearls. Moreover, immunohistochemical studies showed increased expression of vascular endothelial growth factor (VEGF) in the cytoplasm of the neoplastic cells, confirming the tumor as squamous cell carcinoma. Based on the current laboratory findings, the tumor was identified as well-differentiated squamous cell carcinoma.